KONSEPSI ANALISIS KEBUTUHAN LKPD BERBASIS SAINTIFIK MATERI SEJARAH NENEK MOYANG BANGSA INDONESIA DI KELAS X - Ainah Ainah; L.R. Retno Susanti; Umi Chotimah (Akademika : Jurnal Teknologi Pendidikan, 2022)
This study aims to develop teaching materials for student worksheets (LKPD) on the historical material of the ancestors of the Indonesian nation in class X. This research uses the ADDIE model. The stages of this research are the preliminary investigation stage and the prototype stage. Data collection techniques in the form of observation, and questionnaires. The data analysis technique in this study used an instrument sheet in the form of a likert scale with 5 levels of assessment and calculated to see the validity and practicality of the product. The results of the study of 3 expert validators of design, material and language showed that LKPD products were tested for validity with the resulting category which was very valid and the average percentage obtained was 82%. The product practicality test for students through filling out the questionnaire obtained an average very practical assessment of 83%. LKPD book products have been tested to be effective in improving student learning outcomes, as can be seen from the comparison of student scores at the time of pretest then learning to use LKPD in an N-gain score of 0.60 in the medium category. This shows that this LKPD is effectively used to help improve student learning outcomes in history learning, especially the historical material of the ancestors of the Indonesian nation